Attention span and reading comprehension among UiTM TESL postgraduates in Shah Alam / Mohd Azizi Ab. Ghani - Ab. Ghani, Mohd Azizi (2014)
This study investigated students' Attention Span and Reading Comprehension level amongst the sample of 53 full-time TESL postgraduate students from the Faculty of Education, Section 17, UiTM Shah Alam. Using an attention span test and a reading comprehension test, the results were then used to find out the correlation between Attention Span Level and Reading Comprehension Level. The students were also asked to rate their own reading ability. The result from the Self-Reported Reading Ability and Reading Comprehension level were used to find out the correlation between them. The CGPA given by the samples were used as a dependent variable and the Attention Span Level were used as the independent variable in the regression analysis conducted. It was found out that the majority of the samples' Attention Span Level was low but the Reading Comprehension Level was at an advanced level. The correlation between Attention Span Level and Reading Comprehension Level was weak and not significant (rs = 0.180, P> 0.05). This showed that both level didn't correlate with one another. However, the correlation between Self-Reported Reading Ability and Reading Comprehension Level of the students showed a moderate but significant result (rs = 0.366, P>0.05). This proved that the students know how to evaluate reading performance and are aware of their own reading capability. It was also found out that the Attention Span level cannot be used to predict the Achievement which was based on the CGPA. Since the data proved that Attention Span Test were not aligned with the Reading Comprehension Test, future researchers should try other methods and also uses bigger scale sample from different level of education such as primary, secondary, diploma or degree in order to find a better results to investigate the relationship between Attention Span and Reading Comprehension.